The Bro1-like domain-containing protein, AtBro1, modulates growth and abiotic stress responses in Arabidopsis - Mehdi, Syed Muhammad Muntazir; Szczesniak, Michal Wojciech; Ludwików, Agnieszka (Frontiers in Plant Science, 2023)
Abscisic acid (ABA) affects plant physiology by altering gene expression, enabling plants to adapt to a wide range of environments. Plants have evolved protective mechanisms to allow seed germination in harsh conditions. Here, we explore a subset of these mechanisms involving the AtBro1 gene, which encodes one of a small family of poorly characterised Bro1-like domain-containing proteins, in Arabidopsis thaliana plants subjected to multiple abiotic stresses. AtBro1 transcripts were upregulated by salt, ABA and mannitol stress, while AtBro1-overexpression lines demonstrated robust tolerance to drought and salt stress. Furthermore, we found that ABA elicits stress-resistance responses in loss-of-function bro1-1 mutant plants and AtBro1 regulates drought resistance in Arabidopsis. When the AtBro1 promoter was fused to the β-glucuronidase (GUS) gene and introduced into plants, GUS was expressed mainly in rosette leaves and floral clusters, especially in anthers. Using a construct expressing an AtBro1-GFP fusion protein, AtBro1 was found to be localized in the plasma membrane in Arabidopsis protoplasts. A broad RNA-sequencing analysis revealed specific quantitative differences in the early transcriptional responses to ABA treatment between wild-type and loss-of-function bro1-1 mutant plants, suggesting that ABA stimulates stress-resistance responses via AtBro1. Additionally, transcripts levels of MOP9.5, MRD1, HEI10, and MIOX4 were altered in bro1-1 plants exposed to different stress conditions. Collectively, our results show that AtBro1 plays a significant role in the regulation of the plant transcriptional response to ABA and the induction of resistance responses to abiotic stress.